Effect of silica nanoparticles on carbon dioxide separation performances of PVA/PEG cross-linked membranes - Dilshad, Muhammad Rizwan; Islam, Atif; Haider, Bilal; Sajid, Muhammad; Ijaz, Aamir; Khan, Rafi Ullah; Khan, Waheed Gul (Chemical Papers, 2021)
Novel PVA/PEG cross-linked membranes were prepared with (0–20 wt. %) of silica nanoparticles. The presence of both the polymers and additive was confirmed by FTIR analysis. The thermal properties of the membranes were analyzed by TGA and DSC analysis. The morphological and mechanical properties of the membranes were studied by SEM analysis and tensile testing, respectively. The gas permeation performances of the membranes were examined using state-of-the-art gas permeability cell. It was found that permeability of all the gases increased with the increase of silica loading, whereas ideal selectivity of carbon dioxide with respect to nitrogen and methane increased up to 10 wt. % loading and then became nearly constant on further loading. 20 wt. % silica loaded membrane was found to be the best performance membrane. The gas permeability of CO2 was also compared with different gas permeation models and was found to be in close agreement with Maxwell Model. The effect of temperature and pressure of feed gas pressure was also studied on permeation performances and optimum performances were achieved around 65 °C. The gas permeation performances were observed to decrease slightly with the increase in feed gas pressure up to 20 bar which confirms the absence of plasticization phenomenon up to 20 bar. Finally, gas permeation performances were compared with 2008 Robeson trade-off lines and it was found that at 20 wt. % loading, gas permeation performances surpassed the trade-off line for CO2/N2, and for CO2/CH4, the gas permeation performances approached the trade-off line.
CRIS-Team Scopus Importer:2021-03-05
Keywords: CH; CO; CO; Gas separation membranes; N; PEG; PVA; Silica nanoparticles

Electrophoretic deposition of PEEK/bioactive glass composite coatings for orthopedic implants: A design of experiments (DoE) study - Ur Rehman, Muhammad Atiq; Bastan, Fatih Erdem; Haider, Bilal; Boccaccini, Aldo R. (Materials & Design, 2017)
<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">This paper presents a study on the Design of Experiments (DoE) approach to optimize the electrophoretic deposition (EPD) process parameters for PEEK base coatings. PEEK and bioactive glass (45S5 BG) particles were suspended in ethanol and suspensions were stabilized with the help of citric acid. Electric field related parameters were optimized by using Taguchi DoE; an orthogonal array of L15 type with mixed levels of the control factors. Statistical tools were employed to identify the significant factors affecting deposition rate and to quantify the reproducibility of the constant voltage EPD process. It was demonstrated that both deposition voltage and time significantly influence deposition rate. Moreover, statistical confidence was elucidated by Defect Per Million Opportunities (DPMO) model, as proposed in six sigma tools. A pronounced deposition rate was obtained at 100<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;"> <span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">V/cm in comparison to 110<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;"> <span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">V/cm, although the adhesion strength and microstructural homogeneity were lower for 100<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;"> <span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">V/cm. The optimal suspension composition and EPD conditions predicted by DoE were further verified by experiments and qualitative agreement was found between the predicted and experimental data. The experimental results and statistical analyses are discussed based on current knowledge of the EPD of ceramic materials and their co-deposition with polymeric particles.
Keywords: Electrophoretic deposition; Design of Experiment; PEEK; Bioactive glass

Highly permeable innovative PDMS coated polyethersulfone membranes embedded with activated carbon for gas separation - Haider, Bilal; Dilshad, Muhammad Rizwan; Ur Rehman, Muhammad Atiq; Akram, Muhammad Sarfraz; Kaspereit, Malte (Journal of Natural Gas Science and Engineering, 2020)
Innovative asymmetric polyethersulfone (PES) membranes embedded with activated carbon (AC) were synthesized and then surface coated with thin PDMS layer. The membranes were then tested with advanced analytical techniques like FTIR, TGA, SEM and EDX analysis. Thereafter, the membranes were tested for gas permeation analysis with following five gases: carbon dioxide, hydrogen, nitrogen, helium and methane. The effects of embedding AC and feed gas pressure on gas permeation properties were also examined. The permeance of all the gases improved with the embedding of AC in the membrane without much decreasing their ideal selectivity while PDMS coating enhanced the ideal selectivity at the expense of decreasing permeance of all the gases. It was found that 30 wt. % AC embedded PDMS coated PES membrane, having thickness of 80 μm, exhibited the best gas permeation properties for following five pair of gases CO2/N2, CO2/CH4, H2/N2, He/N2 and He/CH4 at 25 °C and 20 bar. The best performing membrane was also tested for long term stability by exposing it with each gas for 96 h. It was also found that the performance of 30 wt % AC embedded membrane, surpassed the 2008 Robeson trade off line for all pair of gases except for CO2/CH4 for which it nearly touched this line. Finally, PDMS coated membranes were also tested with CO2/CH4 (50:50) mixture at high pressure and found that mixed gas permeation properties are considerably lesser than pure gas permeation properties due to possibility of competitive sorption phenomenon between the gases.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Activated carbon; Gas separation membranes; PDMS coating; Polyethersulfone

Highly permeable novel PDMS coated asymmetric polyethersulfone membranes loaded with SAPO-34 zeolite for carbon dioxide separation - Haider, Bilal; Dilshad, Muhammad Rizwan; Ur Rehman, Muhammad Atiq; Vargas Schmitz, Jürgen; Kaspereit, Malte (Separation and Purification Technology, 2020)
Novel asymmetric polyethersulfone membranes loaded with SAPO-34 particles were prepared using phase inversion technique and then surface coated with PDMS using spin coating method. The mixed matrix membranes were then characterized by FTIR, TGA, SEM-EDX and gas permeation analysis. Effect of SAPO-34 loading alongwith operating pressure was also analyzed on gas permeation properties of both coated and uncoated membranes. SAPO-34 loading resulted in improvement of permeability of all the gases without much decrease in CO2 ideal selectivity with respect to methane and nitrogen whereas PDMS coating resulted in improvement of ideal selectivity of CO2 at the expense of decrease of permeance of all the gases. It was found that PDMS coated PES membrane, loaded with 30 wt.% SAPO-34, having thickness of 45 µm, demonstrated high CO2 permeance of 641.77 GPU, CO2/CH4 ideal selectivity of 4.45 and CO2/N2 ideal selectivity of 12.45, respectively at 20 bar and 25 °C. It was found that the performance of this membrane crossed the Robeson upper bound limit 2008 for CO2/N2 separation whereas for CO2/CH4 separation it crossed the previous upper bound limit 1991. Finally, the performance of this membrane was also analyzed under mixed gas conditions for CO2/CH4 separation at high pressure.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Asymmetric; Gas separation membranes; PDMS coating; Polyethersulfone; SAPO-34

Investigation of functional, physical, mechanical and thermal properties of TiO2 embedded polyester hybrid composites: A design of experiment (DoE) study - Munawar, Muhammad; Schubert, Dirk W.; Khan, Shahzad Maqsood; Ur Rehman, Muhammad Atiq; Gull, Nafisa; Islam, Atif; Sabir, Aneela; Shafique, Muhammad; Haider, Bilal; Azam, Mudassar; Khan, Saba Urooge; Voigt, Monika (Progress in Natural Science, 2018)
Keywords: Design of experiment; Titania; Hybrid composites; Polyester

Novel Polydimethylsiloxane membranes impregnated with SAPO-34 zeolite particles for gas separation - Haider, Bilal; Dilshad, Muhammad Rizwan; Akram, Muhammad Sarfraz; Islam, Atif; Kaspereit, Malte (Chemical Papers, 2021)
Novel polydimethylsiloxane membranes impregnated with SAPO-34 zeolite particles were synthesized using solution casting method and then analyzed by FTIR, TGA, SEM, tensile testing and permeation performances with CO2, N2, CH4, O2 and H2. SAPO-34 impregnation resulted in enhancement of both permeability and selectivity of all the gases up to 30 wt.% loading,; and beyond this threshold, further addition resulted in decline in gas permeation performances. On the basis of permeation performances, 30 wt.% filler impregnated membrane was designated as the best performance membrane, which was further chosen to analyze the effect of feed gas pressure. It has been found that gas permeation properties keep on increasing with the increase in feed gas pressure up to 20 bar. The gas permeability results of CO2 were then compared with conventional gas permeability models, and it was found that the gas permeability followed Maxwell Model. The best performance membrane was then tested for equimolar mixture of CO2/CH4 at high pressure and found that mixed gas selectivity was considerably lesser than ideal gas selectivity owing to competitive sorption phenomenon between the gases. Finally, the gas permeation properties of the best performance membrane were compared with 2008 Robeson upper bound limits and found that at 20 bar and 25 °C, the gas permeation properties surpassed the upper bound limits for CO2/N2 and O2/N2 separation and approached near to these limits for H2/N2 and CO2/CH4 separation.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Gas separation membranes; PDMS; SAPO-34